Global virtual teams management system: project manager guide - Hiba Adil Yousif; Ali Yahya Gheni; Yusmadi Yah Jusoh; Nur Ilyana; Mohana Shanmugam (Bulletin of Electrical Engineering and Informatics, 2022)
Global virtual teams (GVTs) are a recent organizational adaptation created to meet the needs of globalizatized marketplace. GVTs are essentially teams that are distributed across national boundaries and concerned through advanced information and communication technology (ICT) such as email, instant messaging, and video conferencing. The research on GVTs is important in the information system (IS) field because GVTs are dependent on information communication technology and the use of other technologies; GVTs also consists of people from different cultures. This paper tried to answer two research questions. The first one is: what are the GVTs problems facing the project manager (PM). A literature review was conducted to answer the first research question. The second one is: how to develop system as a guide for PM. The system was developed by Visual Studio 2019. Online model verification was conducted within 6 experts from IT industry. After developing the system, it was validated by eleven developers (non-functional test/black-box testing) and 3 developers/programmers (functional test/white-box testing) from the same industry. The result of model verification confirmed that the model can help the PM. Also, the non-functional test/black-box testing and functional test/white-box testing was confirmed.